Winter is coming : why Vladimir Putin and the enemies of the free world must be stopped - Kasparov, G. K. (Garri Kimovich); Greengard, Mig (Public Affairs, 2015)
The ascension of Putin to the presidency of Russia in 1999 was a strong signal that the country was headed away from democracy. Now, with his vast resources and nuclear arsenal, Putin is at the center of a worldwide assault on political liberty and the modern world order. Kasparov shows that the collapse of the Soviet Union was not an endpoint, and reveals Putin as an existential danger hiding in plain sight--Publisher description.